ANALISIS EFISIENSI TEKNIS DAN PENDAPATAN USAHATANI PADI PROGRAM BENIH BERSERTIFIKAT: PENDEKATAN STOCHASTIC PRODUCTION FRONTIER - Dwi Rachmina; Maryono Maryono (Jurnal Agribisnis dan Ekonomi Pertanian, 2008)
Indonesian Ministry of Agriculture launched the certified rice seed program in order to increase rice production and productivity where the pilot project was implemented in Karawang. The objectives of this research are to analyze the technical efficiency, structure of cost and income, and to evaluate the implementation of new innovation technology for certified rice seed program. Stochastic frontier production function, with MLE, showed that the technical efficiency has decreased after the implementation of program. The result of technical inefficiency effect before the implementation of program showed that the significant variables were dummy organic and legowo, whereas after the implementation of program were the experience, education, and urea-TSP ratio. This condition showed that the increasing profit was caused by the change of price, not by the increase of productivity. The implementation of farming technology was not successful where only 9.68 percent of respondents used organic fertilizer, 6.45 percent planted young seedlings, 12.90 percent practiced legowo, and 45.16 percent applied fertilizers efficiently.